Hypoglycemic, Antihyperglycemic, and Toxic Effects of Physalis peruviana L. Aqueous and Methanolic Leaf Extracts in Wistar Rats - Kasali FM; Kadima JN; Tusiimire J; Agaba AG (Dove Medical Press, 2022)
Félicien Mushagalusa Kasali,1- 3 Justin Ntokamunda Kadima,3 Jonans Tusiimire,2 Amon Ganafa Agaba4 1Pharm-Bio Technology and Traditional Medicine Center, Mbarara University of Science and Technology, Mbarara, Uganda; 2Department of Pharmacy, Mbarara University of Science and Technology, Mbarara, Uganda; 3Department of Pharmacy, Official University of Bukavu, Bukavu, Democratic Republic of the Congo; 4Department of Pharmacology and Therapeutics, Mbarara University of Science and Technology, Mbarara, UgandaCorrespondence: Félicien Mushagalusa Kasali, Pharm-Bio Technology and Traditional Medicine Center, Mbarara University of Science and Technology, Mbarara, Uganda, Tel +256 750919712, Email felicienkasali@gmail.comBackground: Physalis peruviana L. (Solanaceae) is a plant widely used in traditional medicine systems to manage various diseases, including diabetes mellitus, which remains a global health problem in developing and developed countries. This study aimed to scientifically evaluate its antidiabetic bioactivity and short-term toxicity in rats.Methods: We prepared various doses (100, 200, 400 mg/kg) of aqueous and methanolic leaf extracts for the antidiabetic study, and a dose of 2000 mg/Kg was prepared for the acute toxicity test. The first group that evaluated the hypoglycemic effect consisted of forty normoglycemic Wistar rats aged 7- 8 months old with a weighted average of 265.8 ± 24.6 g. The second group consisted of intraperitoneal glucose-loaded male animals to evaluate the antihyperglycemic effect. The third group contained two groups of normoglycemic female rats (n = 3), aged 3 and 4 months old (weight average: 187.45 ± 14.82 g), treated for 14 days with aqueous and methanolic extracts (2 g/kg b.w) to assess mortality and toxic effects. Blood samples were taken at 30, 60, 90, and 120 min post-treatment in hypoglycemic and antihyperglycemic evaluations. Glibenclamide (5 mg/kg) was used as a reference drug. The control animals in each group did not receive the extracts.Results: In hypoglycemic rats, 100 mg/kg of aqueous and methanolic extracts significantly lowered the fasting blood glucose level by 13.92% (p < 0.0001) and 21.95% (p < 0.01), respectively, compared to the control group. In glucose tolerance test group, methanolic extracts significantly reduced hyperglycemia by 54.55% (p < 0.0001), 46.50% (p < 0.0001), 39.78% (p < 0.0001) at 400, 200 and 100 mg/kg b.w, respectively, compared to control; aqueous extract 400 mg/kg reduced hyperglycemia by 39.44% (p < 0.05). At the 2000 mg/kg dose, leaf aqueous and methanolic extracts did not show any signs of intoxication and mortality.Conclusion: Crude aqueous and methanolic leaf extracts of P. peruviana ambrosioides appeared safe at 2000 mg/kg and have bioactivity in controlling the blood glucose levels, supporting their use in treating diabetes.Keywords: Physalis peruviana, leaf extracts, antidiabetic bioactivity, toxicity, rats